Conserved Pheromone Production, Response and Degradation by Streptococcus mutans - Ricomini Filho, Antonio Pedro; Khan, Rabia; Åmdal, Heidi Aarø; Petersen, Fernanda C. (Frontiers in Microbiology, 2019)
Streptococcus mutans coordinates competence for natural transformation and bacteriocin production via the XIP and CSP pheromones. CSP is effective in inducing bacteriocin responses, but not competence in chemically defined media (CDM). This contrasts with XIP, which induces competence in CDM, but also stimulates late expression of bacteriocin genes. Inter-connections between the pathways activated by the two pheromones are characterised in certain detail in strain UA159, but it is mostly unknown whether such findings are representative for the species. Here, we used bioassays based on luciferase reporters for the bacteriocin gene cipB and the alternative sigma factor sigX to investigate S. mutans isolates for production and response to CSP and XIP pheromones in CDM. Endogenous CSP was undetectable in the culture supernatants of all tested strains. During optimization of the bioassay using the cipB reporter, we discovered that the activity of CSP used as a standard was reduced over time during S. mutans growth. Using a FRET-CSP reporter peptide, we found that S. mutans UA159 was indeed able to degrade CSP, and that such proteolytic activity was not significantly different in isogenic mutants with deletion of the protease gene htrA, or the competence genes sigX, oppD, and comR. CSP proteolysis was also detected in all the wild type strains, indicating that such activity is conserved in S. mutans. For the XIP pheromone, endogenous production was observed in the supernatants of all 34 tested strains at peak concentrations in culture supernatants that varied between 200 nM and 26000 nM. Transformation in the presence of exogenous XIP was detected in all, but one, of the isolates. The efficiency of transformation varied, however, among the different strains, and for those with the highest transformation rates, endogenous XIP peak concentrations in the supernatants were above 2000 nM XIP. We conclude that XIP production and inducing effect on transformation, as well as proteolytic activity leading to the inactivation of CSP are conserved functions among different S. mutans isolates. Understanding the functionality and conservation of pheromone systems in S. mutans may lead to novel strategies to prevent or treat unbalances in oral microbiomes that may favour diseases.